Design and Synthesis of Bis Thiazol-2-ylidenes - Sravanthi, T.V.; Reddy Pottem, Madhusudhana; Manju, S.L. (Asian Journal of Chemistry, 2013)
A series of novel hitherto unreported 4,4'-[N,N'-bis(3-phenyl-4-(4-substituted phenyl)-thiazol-2(3H)-ylidene)]methylenedianiline derivatives has been synthesized by the heterocyclization between the bis-1,3-disubstituted thiourea and substituted acetophenones in presence of iodine. Both conventional and non-conventional methods have been used for the synthesis of the targets. All the synthesized compounds were confirmed by spectral analysis.